Decarbonizing Building and Transport Sectors in Thailand towards Net Zero Emissions 2050 - Lorm, Rathana; Limmeechokchai, Bundit (Journal of Architectural/Planning Research and Studies (JARS), 2025)
The building and transport sectors in Thailand are two major GHG emissions contributors in terms of direct and indirect emissions through energy use. Accelerating the transition to low-emissions technology is necessary to mitigate the rise in global temperatures. This study explores three scenarios, the Reference (REF), the Existing Policy (EXP), and the Deep Decarbonized (DDC) scenarios, using the LEAP-NEMO analysis tool. The REF scenario is formulated under a business-as-usual assumption without considering any policy or mitigation implementation. The EXP scenario is developed by the adoption of the latest government energy and climate change mitigation policies. The DDC scenario is constructed by increasing the ambition of the climate policies regarding energy efficiency improvement in the building sector, increasing battery electric vehicles (BEVs) and hydrogen fuel cell electric vehicles (HFEVs) in the transport sector, and fully integrating renewable energy in electric power generation through the optimization method in LEAP-NEMO. The outcomes illustrate that, in the EXP scenario, total energy consumption in 2050 for both the building and transport sectors would be reduced by 26.04% compared to the REF scenario, and GHG emissions would be reduced by 31.16%. Under the DDC scenario, energy saving and GHG emissions mitigation in 2050 would be around 41.46% and 86.85%, respectively, compared to the REF scenario. The DDC scenario shows that the net zero emissions target in 2050 is feasible for Thailand. However, to avoid carbon lock-in, policy measures on decarbonized building and transport sectors are critical in this decade to achieve net zero emissions in 2050.